Effectiveness of E-Module Flipbook Based on Guided Inquiry Learning on Acid Base Material at MA Almuhtadi - Fatayah, Fatayah; Ilmah, Mashfufatul; Chandrika, Nadya Okta (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2025)
One topic that is often considered difficult by students is acid and base material. Based on the results of the pre-research, it shows that students of MA Almuhtadi have difficulty with acid and base material. One promising innovation is the use of e-module flipbooks. However, good media needs to be combined with the right learning approach. One approach that has proven effective is guided inquiry learning. This study was conducted to determine the effectiveness of e-module flipbooks based on guided inquiry learning in improving student learning outcomes in acid and base material. The research design used in this study was a pre-experiment with a one group pretest-posttest design. Analysis of test result data was carried out using a paired t-test (for normal data) or Wilcoxon test (non-normal data). If the results obtained show a difference between before and after learning using the e-Module Flipbook based on Guided Inquiry Learning, an effectiveness test was carried out using the N-Gain score. The results of the normality test showed that the data was normally distributed. The results of the paired t-test sig. 0.000 <0.05 (there is a difference in the use of e-Module Flipbook based on Guided Inquiry Learning). The results of the N-Gain test obtained a value of 75%, meaning that the use of the Flipbook e-Module based on Guided Inquiry Learning for Acid-Base material is quite effective